Conversor CC-CC bidirecional DAB monofásico baseado na célula de comutação de três estados - Mazza, Luan Carlos dos Santos (2014)
This work presented is DC-DC isolated ZVS Bidirectional Dual Active Bridge (DAB) single phase converter, based three-state switching cell is presented. The proposal is to apply it in photovoltaic systems with battery bank into smart networks. Basically the drive control is the duty cycle (D) of the switches and the Phase Shift (φ) of the fundamental tensions between the bridges. The gyrator modeling of the converter is presented, highlighting its natural operating characteristic as gyrator. Shows the qualitative and quantitative analysis of the converter, realizing the full study of the stages of operation of the topology and checking all sixteen regions of operation. To obtain the regions of soft-switching, the fundamental model is applied. The design procedure of the converter is presented, and the results of simulations. A 2kW prototype was developed, aimed at obtaining experimental results validate the theoretical analysis